Utilization Of Rhizophora Stylosa Bark For Natural Dyeing On Cotton Batik Fabric - Fariz Al Hazmi; Ataswarin Oetopo (Institut Seni Indonesia Yogyakarta, 2022)
The Rhizophora stylosa mangrove or commonly known as Red Mangrove grows in coastal areas with a saltwater and muddy environment. Natural dyes are extracted from such plant parts as roots, leaves, flowers, stems, and fruits. Natural dyes have distinctive colors and are environmentally friendly compared to synthetic dyes. The use of such natural dyes as mangroves can contribute to the green movement by minimizing the number of pollutants. The objective of this study was to analyze the result of Rhizophora stylosa mangrove stem bark color and its quality in cotton batik fabric. The mangrove stem bark is applied as the raw material for natural dyes. The bark is extracted by boiling it to obtain a natural dye solvent. The dye is tested on cotton-based fabrics by mordanting or fixation using alum (KAI(SO4)21∙2H2O), calcium oxide (Ca(OH)2), and ferrous sulfate (FeSO4). Red mangrove bark (Rhizophora stylosa) can produce natural colors of grey, brown, and peach on fabrics made of natural fibers (cotton fabrics) in batik. The hue and color depend on the type of the applied fixative material and the temperature in the process of boiling the fabric to release the wax on the batik (lorod). This research highlight that the red mangrove (Rhizophora stylosa) can be used as a dye in batik-making.